LOUGHLIN, M. (2022). Against Constitutionalism. Cambridge, Massachusetts: Harvard University Press. - Navajas Gómez de Aranda, Santiago (Daimon Revista Internacional de Filosofia, 2024)
Reseña de LOUGHLIN, M. (2022). Against Constitutionalism. Cambridge, Massachusetts: Harvard University Press.